2019 energy benchmarking data for LEED-certified buildings in Washington, D.C.: Simulation and reality. (October 2021) - Hu, Ming
Abstract: This study aims to understand the actual performance difference between LEED buildings and non-LEED buildings. Since 2012, the District of Columbia (DC) has amended regulations so that all buildings must report their building energy use. We have cross-referenced the most recently published data of the 2019 DC energy benchmarking database with the U.S. Green Building Council's LEED project database to identify DC properties in both databases that are expected to reduce building operating energy use and greenhouse gas emissions. We compared LEED office buildings and non-LEED-certified office buildings using their reported operating source and site energy use intensity (EUI). The results show that LEED office buildings do not perform better at any of the certified levels. On the contrary, those reported LEED buildings collectively use 17% more source energy and 13% more site energy than non-LEED buildings. Among the different LEED levels, LEED Silver appears to perform slightly better than the other LEED levels. Meanwhile only around 33% of qualified LEED office buildings reported their actual energy use according to the DC regulation. The purpose of this study is not to criticize the LEED rating system; instead, we want to improve the system in order to meet DC's carbon neutrality goal. To this extent, we conclude that the U.S. LEED rating system can benefit from learning from other green building rating systems that include reporting and verification as prerequisite requirements. Highlights: LEED buildings collectively use 17% more source energy and 13% more site energy than non-LEED buildings. LEED Silver appears to perform slightly better than the other LEED levels. Only around 33% of qualified LEED office buildings reported their actual energy use.